Cost modelling for cloud computing utilisation in long term digital preservation - Shehab, Essam; Sanya, Isaac; Badawy, Mohamed; Ocal, Fatma; Namiesnik, Bartosz; Morineau, Julien; Odika, Stephen; Fernandez Ortiz, Zaira (Cranfield University Press, 2013)
The rapid increase in volume of digital information can cause concern among organisations regarding manageability, costs and security of their information in the long-term. As cloud computing technology is often used for digital preservation purposes and is still evolving, there is difficulty in determining its long-term costs. This paper presents the development of a generic cost model for public and private clouds utilisation in long term digital preservation (LTDP), considering the impact of uncertainties and obsolescence issues. The cost model consists of rules and assumptions and was built using a combination of activity based and parametric cost estimation techniques. After generation of cost breakdown structures for both clouds, uncertainties and obsolescence were categorised. To quantify impacts of uncertainties on cost, three-point estimate technique was employed and Monte Carlo simulation was applied to generate the probability distribution on each cost driver. A decision support cost estimation tool with dashboard representation of results was developed.
Keywords: Cloud Computing; Cost Modelling; Uncertainties; Long-Term Digital Preservation